(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2025)
archivia is a choreographic research project that aims to transmit and transform the repertoire produced between the 1980s and the early 2000s by choreographer Monica Francia. The project was born in 2021 from the desire of Zoe Francia Lamattina, artist and performer, daughter of Monica Francia. This text, written from the point of view of the project’s dramaturg, aims to show how it is possible to archive a choreographic repertoire without putting written, recorded, fixed materials before bodily experience, body-to-body transmission, partial and fictitious narratives. The archiving thus takes place through the transmission, repetition and transformation of all the bodies involved in the process and of the repertoire itself, up to the original turbulence that agitates the past and opens up still possible futures. Disrupting the patriarchal and parricidal principle of the archive, the relationship between generations and between different temporalities remains complex and conflictual, never resolving itself in the historical present of a linear and definitive narrative.